Determinants that influencing inflation rate in Malaysia (1988 – 2018) / Izwin Saifullizan - Saifullizan, Izwin (Faculty of Business and Management, 2020)
The aim of this study is to investigate the relationship between selected macroeconomic determinants with inflation rate in Malaysia. The study used model of Multiple Linear Regression in order to find the relationship between gross domestic product rate, unemployment rate, exchange rate and interest rate towards inflation rate. The annually data was collected from 1988 until 2018. From the result, it reveals that gross domestic product rate and unemployment rate has negative insignificant relationship toward inflation rate while exchange rate and interest rate has negative significant relationship towards inflation rate. These results further our discussion of the relationship between gross domestic product rate, unemployment rate, exchange rate and interest rate towards inflation rate thus this study should be useful for public, industries and policymakers.